Fusaric acid induces NRF2 as a cytoprotective response to prevent NLRP3 activation in the liver derived HepG2 cell line. (March 2019) - Sheik Abdul, Naeem; Nagiah, Savania; Chuturgoon, Anil A.
Abstract: Fusaric acid (FA) is a neglected fusarium mycotoxin despite its ubiquitous presence. FA is a niacin related compound and mediates toxicity via oxidative stress and mitochondrial dysfunction. The NLRP3 inflammasome is a multiprotein scaffold that plays a key role in IL-β maturation. We investigated the effects of FA on IL-1β processing, NRLP3 inflammasome priming and activation along with the potential of FA to initiate cytoprotective mechanisms using spectrophotometry, luminometry, qPCR and western blots in the HepG2 liver cell line. FA disrupted synthesis and maturation of IL-1β by inhibiting NRLP3 priming and activation. Further experimentation revealed an up-regulation of NRF2 with concomitant elevation in the anti-oxidant enzyme SOD2 and autophagy markers suggesting that FA induces NRF2 cytoprotective programs in these cells. We conclude that FA attenuates inflammasome priming and activation and sheds light on the immunosuppressive potential of FA in liver cells. Highlights: Fusaric acid (FA), a foodborne mycotoxin, is a putative mitochondrial toxin. FA down regulates NLRP3 inflammasome priming and activation in liver cells. FA initiates the NRF2 cytoprotective program in liver cells. Enhanced mitophagy attenuates inflammation in FA stimulated liver cells.